Penerapan Prinsip Manajemen Sumber Daya Insani di Kampung Cokelat Blitar - Husna, Nadya Amira; Latifah, Nur Aini (Jurnal Iqtisaduna, 2018)
Along with developing era, economic activity is also developed, even islamic economic follows the development too. As muslim, it is a must to stay applying Islam lesson in daily life, it includes term of management activity that is going on. Management of company consists of management of human resouce that can be integrated with Islam lessons and sourced from Al-Qur’an and Hadist. Implementation of management based on syariah commonly is only done by the company that the owner is a muslim who obligates whole of his or her employees follows syariah regulations. One of them is this Kampung Coklat’s Blitar company. This research uses qualitative methods, with data collection conducted through interviews and in-depth observation and during the period. The study found that the implementation of Shariah-based human resource management in Kampung Coklat Blitar included recruitment process, the selection process (must follow some tests), training and development (religious), and performance appraisal (using work and behavior). The results also show that this Blitar Coklat Village company in the implementation of syariah based human resource management is in accordance with the teachings of Islam. By implementing rewards to employees who behave well.